TEACHING BIOSCIENCE IN PRIMARY AND MIDDLE SCHOOL AND CHILDREN'S ECOLOGICAL AWARENESS - Pytel, Krzysztof; Piaskowska, Małgorzata; Migo, Piotr (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
In the article, the aims of teaching bioscience in primary and middle school have been introduced. Core curriculum has been mentioned as well, and the tools that may be used by a teacher to convey theory and practical knowledge in the most efficient way  have been discussed. Furthermore, it has been noticed that various ecological ventures have a positive impact on children's ecological awareness. In the second part of the article, results of surveys conducted among primary and middle school students have been introduced. It embraces also questions and answers, in which children describe their knowledge level about the condition of environment and talk about their attitude towards taking care of nature, and what are the stimuli of such demeanours. In addition, the task of surveys was to find out which issues teachers pay particular attention to. The last two questions were to check the knowledge.